The United States: The Role of the Brothers of Holy Cross - Armstrong, C.S.C., Philip C. (Catholic Education: A Journal of Inquiry and Practice, 2007)
The Congregation of Holy Cross, the founding religious community behind the University of Notre Dame, had its origin in the ranks of diocesan clergy in France. This article chronicles the early history of the congregation, struggles between priests and its brothers, and its movement into the ministry of Catholic education.